A framework to arrive at a unique performance measurement score for the balanced scorecard. (16th April 2009) - Punniyamoorthy, M.; Murali, R.
For any business activity, it is essential to identify the required performance measures which have strategic implications. The Balanced Scorecard (BSC) is a very useful performance measurement system. But there is no distinction made with regard to the importance provided to the perspectives under BSC. Furthermore, for some metrics, the actual performance may be greater than the targeted performance and for some, it is less. This makes it unclear for decision makers whether the firm had achieved the strategic intent in totality or not. In this article, the weightages for the perspectives and subcriteria are arrived at through the fuzzy Analytical Hierarchy Process (AHP) and an analytical expression developed by the author. This model further helps in arriving at a unified score to portray the overall performance of the organisation. The developed model is validated through a real-life example.